Executive Entrenchment in Founder‐Managed Firms: An Empirical Study from China. (1st July 2016) - He, Xiaogang; Karri, Ranjan; Zhang, Yuanfei; Mei, Lin
Abstract : We study the relationship between past firm performance, ownership concentration, board independence, and industry competition on the likelihood of dismissal for both founder and nonfounder executives using a panel data set of Chinese founded firms during 1999–2007. Results indicate a persistent presence of entrenchment of founder executives. Compared with the founder, the nonfounder executive is more likely to be dismissed following periods of poor firm performance combined with ownership concentration and board independence except under high levels of industry competition when founder executives are more likely to be held accountable through dismissal by independent boards.